2020
DOI: 10.3389/fonc.2020.00495
|View full text |Cite
|
Sign up to set email alerts
|

Abiraterone Rechallenge Based on Sequential Testing of Androgen Receptor Splice Variant 7 Expression in Circulating Tumor Cells: A Case Report

Abstract: Serial analysis of circulating tumor cells (CTCs) such as androgen receptor splice variant 7 is useful in selecting treatments for castration-resistant prostate cancer (CRPC). We report a case who had been positive for androgen receptor splice variant 7 in CTCs before docetaxel, and was subsequently treated with abiraterone rechallenge because of the negative conversion of androgen receptor splice variant 7 following docetaxel. Although, the rechallenge of anti-androgen agent based on CTCs analysis is expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In a previous study conducted at our facilities and affiliated hospitals, we analyzed PFS in mCRPC patients with bone metastases treated with ENZ and demonstrated that a negative CTC status at baseline before ENZ treatment was a significant predictor for ENZ efficacy [10]. It has already been reported that chronological monitoring of CTCs is very effective for evaluating possible treatments and their efficacy in mCRPC [15][16][17]. The purpose of the current study is to establish the relationship between the chronological detection of CTCs during ENZ treatment and OS by setting a longer observation period and performing CTC detection at 3 months after ENZ introduction.…”
Section: Introductionmentioning
confidence: 98%
“…In a previous study conducted at our facilities and affiliated hospitals, we analyzed PFS in mCRPC patients with bone metastases treated with ENZ and demonstrated that a negative CTC status at baseline before ENZ treatment was a significant predictor for ENZ efficacy [10]. It has already been reported that chronological monitoring of CTCs is very effective for evaluating possible treatments and their efficacy in mCRPC [15][16][17]. The purpose of the current study is to establish the relationship between the chronological detection of CTCs during ENZ treatment and OS by setting a longer observation period and performing CTC detection at 3 months after ENZ introduction.…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, though, abiraterone and enzalutamide were confirmed to significantly prolong the survival of men with mCRPC after docetaxel (59,60). Detection of androgen-receptor splice variant 7 (AR-V7) was proved to be associated with resistance to abiraterone and enzalutamide (61), while the negative conversion of AR-V7 following docetaxel has been reported, the discovery may explain the benefit of abiraterone and enzalutamide following docetaxel, and consequently abiraterone rechallenge may function as usual (62). On the other hand, enzalutamide showed a modest response rate in castration-resistant prostate cancer patients progressing after the use of abiraterone, similar clinical outcomes were observed in the application of abiraterone after enzalutamide failure, which implied cross-resistance was not inevitable (63,64).…”
Section: Discussionmentioning
confidence: 99%